Transplant experiments uncover Baltic Sea basin-specific responses in bacterioplankton community composition and metabolic activities - Lindh, Markus V.; Figueroa, Daniela; Sjöstedt, Johanna; Baltar, Federico; Lundin, Daniel; Andersson, Agneta; Legrand, Catherine; Pinhassi, Jarone (Frontiers in Microbiology, 2015)
Anthropogenically induced changes in precipitation are projected to generate increased river runoff to semi-enclosed seas, intensifying loads of terrestrial dissolved organic matter and decreasing salinity. To determine how bacterial community structure and functioning adjust to such changes, we designed microcosm transplant experiments with Baltic Proper (salinity 7.2) and Bothnian Sea (salinity 3.6) water. Baltic Proper bacteria generally reached higher abundance than Bothnian Sea bacteria in both Baltic Proper and Bothnian Sea water, indicating a higher adaptability. Moreover, Baltic Proper bacteria growing in Bothnian Sea water consistently showed highest bacterial production and beta-glucosidase activity. These metabolic responses were accompanied by basin-specific changes in bacterial community structure. For example, Baltic Proper Pseudomonas and Limnobacter populations increased markedly in relative abundance in Bothnian Sea water, indicating replacement. In contrast, Roseobacter and Rheinheimera populations were stable or increased in abundance when challenged by either of the waters, indicating adjustment. Transplants to Bothnian Sea water triggered the initial emergence of particular Burkholderiaceae populations, and transplants to Baltic Proper water triggered Alteromonadaceae populations. Notably, in the subsequent re-transplant experiment, the original triggering, or priming effect, resulted in further increases to dominance of these populations. Correlated changes in community composition and metabolic activity were observed only in the transplant experiment, and only at relatively high phylogenetic resolution. This suggested an importance of successional progression for interpreting relationships between bacterial community composition and functioning. We infer that priming effects on bacterial community structure by natural episodic events or climate change induced forcing could translate into long-term changes in bacterial ecosystem process rates.